Tannery wastewater treatment: conventional and promising processes, an updated 20-year review - Jun Zhao; Qinglian Wu; Yuling Tang; Jianfei Zhou; Hongguang Guo (Journal of Leather Science and Engineering, 2022)
Abstract Mismanagement of various wastes especially waste water produced by tanning processes has caused serious environmental problems and ultimately impaired human health. Constant efforts have been making to alleviate the pollution of tannery wastewater (TWW), yet terminal treatment still takes dominance. In this review, research on TWW treatment from 2000 to 2021 was summarized, and main methods such as coagulation and flocculation, adsorption, biological treatment, membrane filtration, advanced oxidation process were briefly discussed. More detailed introduction was given to the method of electrochemical treatment since it has excellent performance such as environmental friendliness and high efficiency, hence attracting more and more research attention in recent years. In view of the harsh physi-chemical conditions of TWW, integrated or combined treatment methods are accordingly recommended with better performance and multi-function, however comprehensive studies on optimization of methods combination and cost-effectiveness are needed. The certain issues that the residue Cr in treatment sludge and high salinity in effluent still remain were put forward in this work and potential solutions were provided. Moreover, this review proposed the perspective that realizing multi-function, recycling, and intensification should be the developing direction for future TWW treatment. This review is expected to provide a general guide for researchers who aspire to ameliorate TWW pollution problems and understand various methods utilized in this field. Graphical abstract